RoboParty: 20 Editions Building Robots and Motivating Youngsters for Science, Technology, Engineering, and Mathematics Subjects [Competitions] - Ribeiro, A. Fernando; Lopes, Gil; Pereira, Nino; Cruz, Jose (IEEE robotics & automation magazine, 2022)
Robotic products and services are quickly getting into people's homes, and it is important to prepare the youngsters for new challenges. One way to motivate them is through competitive events [1] . Back in 2006, the Laboratory of Automation and Robotics [2] at the University of Minho [3] , Guimarães, Portugal, created a new event called RoboParty [4] . The main objective is to teach youngsters how to build and program a robot from scratch in a collaborative, fun, and friendly environment. The first edition was held in 2007. Every year the event attracts up to 500 people from different countries. With 13 editions held at the University of Minho, three in Lisbon, and four abroad (in Brazil, Germany, Canada, and Denmark), this event is internationally recognized for its new approach toward learning robotics.